Tuneable multidirectional mechanical attributes of novel sectionally nonlinearly functionally graded femur and cranial bone implants with triply periodic minimal surfaces - Nguyen Van Viet; Wael Zaki; Marwan El-Rich (PLoS ONE, 2025)
Sectionally nonlinearly functionally graded (SNFG) structures with triply periodic minimal surface (TPMS) are considered ideal for bone implants because they closely replicate the hierarchical, anisotropic, and porous architecture of natural bone. The smooth gradient in material distribution allows for optimal load transfer, reduced stress shielding, and enhanced bone ingrowth, while TPMS provides high mechanical strength-to-weight ratio and interconnected porosity for vascularization and tissue integration. Wherein, The SNFG structure contains sections with thickness that varies nonlinearly along their length in different patterns. And TPMS scaffolds are smooth, porous structures that repeat in three dimensions and have zero mean curvature, offering high surface area and tuneable properties. This study presents a novel design and numerical analysis of SNFG titanium alloy Ti6Al4V femur and cranial bone implants incorporating TPMSs. The accuracy of the numerical model is validated through experiments and force-reaction analysis in terms of elastic stiffness of the white Polylactic Acid (PLA)-based SNFG femur and cranial bone implants, demonstrating good agreement among methods, having a maximum percentage difference of 15.6%. It is found that among various TPMS topologies, the gyroid structure is the most suitable candidate for manufacturing SNFG bone implants, offering superior multidirectional mechanical performance. Interestingly, the anisotropy and magnitude of elastic stiffness can be tailored to closely match natural bone by adjusting the gradient index and trabecular part length while maintaining a yield strength higher than that of bone. Additionally, during service, the implant may be subjected to an impact that generates mechanical waves propagating through its structure. These waves transmit the force impulse and induce the propagation of mechanical stress throughout the implant body. The result indicates that increasing the gradient index reduces shear and longitudinal stress wave velocities with minimal impact on wave velocity anisotropy, a key factor in enhancing implant longevity and performance. And, TPMS implants exhibit extreme multiaxial yield strength anisotropy, but it can be accurately captured using the extended Hill’s criterion, which provides a reliable and cost-efficient method for constructing the critical yield surface of SNFG femur and cranial titanium implants, helping to prevent permanent plastic deformation during service. Overall, this work lays the foundation for futuristic optimization approach aimed at designing ideal SNFG titanium femur and cranial bone implants with TPMSs for biomedical applications.